2022
DOI: 10.1038/s41419-022-04955-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic pretreatment attenuates liver ischemia–reperfusion injury by Farnesoid X receptor activation

Abstract: Prophylactic antibiotics (Abx) are used before liver surgery, and the influence of antibiotic pretreatment on hepatic ischemia–reperfusion injury (IRI) remains unclear. Hence, we explored the impact of Abx pretreatment on hepatic IRI in the present work. The gut microbiota has an essential role in hepatic bile acid (BA) metabolism, and we assumed that depletion of the gut microbiota could affect the composition of hepatic BAs and affect liver IRI. The IRI model demonstrated that Abx pretreatment attenuated liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…We also found that GEBE treatment increases the abundances of Lactobacillus salivarius and Mucispirillum schaedleri by means of LEfSe (Figure 2D). In a recent study, Lactobacillus salivarius influenced glucose metabolism in diabetic mice by increasing the expression of glucose transporter protein 2 in human intestinal epithelial cells (Hsieh et al, 2020;Wang et al, 2022). Furthermore, Mucispirillum schaedleri has a protective effect against Salmonella-induced colitis in mice (Herp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that GEBE treatment increases the abundances of Lactobacillus salivarius and Mucispirillum schaedleri by means of LEfSe (Figure 2D). In a recent study, Lactobacillus salivarius influenced glucose metabolism in diabetic mice by increasing the expression of glucose transporter protein 2 in human intestinal epithelial cells (Hsieh et al, 2020;Wang et al, 2022). Furthermore, Mucispirillum schaedleri has a protective effect against Salmonella-induced colitis in mice (Herp et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…thereby reduces inflammation and insulin resistance (Chen et al, 2019;Xing et al, 2020;Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular assays. Cellular functional assays, including the assessment of cell proliferation through EdU (5-ethynyl-2'-deoxyuridine) staining of cell nuclei, "Transwell" in vitro cell migration and "Matrigel Transwell" in vitro cell invasion, in vitro capillary tube formation, nuclear TUNEL staining assay, JC-1 staining of mitochondrial depolarization the Caspase-3 and the Caspase-9 activity assays were described early [12,13,[29][30][31]. qRT-PCR (quantitative reverse transcription polymerase chain reaction) and Western blotting assays have been previously detailed in earlier publications [20,32,33].…”
Section: Methodsmentioning
confidence: 99%